COVID-19 vaccination telephone outreach: an analysis of the medical student experience. Issue 1 (31st December 2023) - Wu, James F.; Abenoza, Nathalie; Bosco, Julia M.; Minshew, Lana M.; Beckius, Anna; Kastner, Mandy; Hilgeman, Brian; Muntz, Martin D.
ABSTRACT: Introduction: The COVID-19 pandemic diminished opportunities for medical students to gain clinical confidence and the ability to contribute to patient care. Our study sought out to understand the value of telephone outreach to schedule COVID-19 vaccines on medical student education. Materials and Methods: Forty students engaged in telephone outreach targeting patients aged 65+ without active patient portals to schedule COVID-19 vaccines. Data consisted of a single administration retrospective pre/post survey inquiring about what students learned, expectations, other health-care processes that would benefit from outreach, and interest in a population health elective. Likert items were analyzed and open response analysis involved inductive coding and generation of thematic summaries by condensing codes into broader themes. Demographic data of patients called and subsequently received the vaccine were also collected. Results: There were 33 survery respondents. There was a statistically significant increase in net comfortability for pre-clerkship students for documenting in Epic, providing telehealth care, counseling on common health-care myths, having challenging conversations, cold-calling patients, and developing an initial trusting relationship with patients. The majority called and who received the vaccine were non-Hispanic Black, within the high SVI category, and had Medicare and/or Medicaid. Qualitative data showed that students emphasized communication, the role of trusted messengers, the need to be open minded, and meeting patients where they are. Discussion: Engaging students in telephone outreach early in the COVID-19 pandemic provided students the opportunity to develop their skills as physicians-in-training, contribute to combating the ongoing pandemic, and add value to the primary care team. This experience allowed students to practice patience, empathy, and vulnerability to understand why patients had not received the COVID-19 vaccine; this was an invaluable experience that helped students develop the skills to become empathetic and caring physicians, and supports the continued role of telehealth in future medical school curriculum.